Effects of combined organic acid treatments during the cutting process on the natural microflora and quality of chicken drumsticks. (September 2016) - Zhu, Yuanting; Xia, Xiaolong; Liu, Aiping; Zou, Likou; Zhou, Kang; Han, Xinfeng; Han, Guoquan; Liu, Shuliang
Abstract: Reducing the microbial load on broiler chicken carcasses at each stage of poultry meat processing, is highly important for hygienic meat production. This study was conducted to assess the efficacy of various combined organic acid treatments during the cutting process on the microbial decontamination of chicken drumsticks. Changes in naturally occurring microflora before and after treatment were analyzed through microbiological counting and polymerase chain reaction–denaturing gradient gel electrophoresis (PCR-DGGE). Results revealed that the most effective treatments obtained through the combination of orthogonal design and sensory evaluation were as follows: 0.5% lactic acid (w/v), 1% citric acid (w/v), and spray-washing for 30 s. Microbiological counting results and PCR-DGGE analysis indicated that the microbial load on the chicken drumsticks decreased significantly after the treatment was administered. The treatment did not affect the physicochemical properties and sensory attributes of the quick-frozen chicken drumsticks during storage. Therefore, the proposed technique could be used to improve the microbial quality of chicken drumsticks. The technique could also be employed in poultry meat production chains. Highlights: Combined organic acid-based spray-washing was used in the cutting process. Decontamination efficacy of combined organic acid treatment was estimated. Natural microflora on drumsticks before and after treatment was analyzed by PCR-DGGE. The microbial load on chicken drumsticks decreased significantly after treatment. Combined organic acid treatment did not affect the quality of chicken drumsticks.